2005
DOI: 10.1093/intimm/dxh228
|View full text |Cite
|
Sign up to set email alerts
|

CD83 localization in a recycling compartment of immature human monocyte-derived dendritic cells

Abstract: Dendritic cells (DC) change their phenotype and functional properties during maturation. CD83 cell surface expression is induced on mature DC (mDC). In this study, we investigated intracellular CD83 localization and transport in human monocyte-derived DC. The enhanced level of CD83 cell surface expression in mDC resulted predominantly from increased protein synthesis, and in addition from regulated intracellular transport of CD83 protein. An internal pool of CD83 protein is present in immature DC (iDC). Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 36 publications
(40 reference statements)
4
36
2
Order By: Relevance
“…Indeed increased surface expression of CD83 in DCs from WT mice could be induced already 2 minutes after the addition of the RyR1 agonist caffeine. These results are in line with the finding that CD83 molecules recycle between endosomes and the cell surface (Klein et al, 2005); in endosomes they co-localize with MHC class II molecules and we have previously shown that pharmacological stimulation of RyR1 results in the rapid expression of pre-formed MHC class II molecules on the cell surface (Vukcevic et al, 2008). Taken together these results support the observations that DC maturation results from the convergence of different signals arising from cytokine release, RyR1-activation and NFkB translocation (Bracci et al, 2007;Baeuerle and Henkel, 1994;Frantz et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed increased surface expression of CD83 in DCs from WT mice could be induced already 2 minutes after the addition of the RyR1 agonist caffeine. These results are in line with the finding that CD83 molecules recycle between endosomes and the cell surface (Klein et al, 2005); in endosomes they co-localize with MHC class II molecules and we have previously shown that pharmacological stimulation of RyR1 results in the rapid expression of pre-formed MHC class II molecules on the cell surface (Vukcevic et al, 2008). Taken together these results support the observations that DC maturation results from the convergence of different signals arising from cytokine release, RyR1-activation and NFkB translocation (Bracci et al, 2007;Baeuerle and Henkel, 1994;Frantz et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…2B). We also identified an EGFP ϩ mCD83 Ϫ DC population that represents immature DCs, consistent with previous reports in which intracellular pools of CD83 were found in the Golgi complex and endocytic vesicles of immature and mature DCs (33,34). However, in contrast to the findings of Cao et al (34), we did not detect CD83 promoter activity in CD11c Ϫ monocytes/macrophages (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the increase in the binding of CD22, or the ␣2,6-specific plant lectin SNA, did not correlate with the expression of the enzyme involved in the synthesis of its glycan, ST6Gal-1, which decreased dramatically. This could be explained by the maturation-triggered mobilization of molecules stored in granules, a phenomenon that has been previously described on DC (56,57), and needs to be further investigated. The interaction between DC and B lymphocytes has been shown to result in multiple effects, such as the inhibition of B cell apoptosis (58), blockage of the production of IgE (59), or Ag presentation (60).…”
Section: Discussionmentioning
confidence: 79%